PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) TERHADAP HASIL BELAJAR SISWA DITINJAU DARI KEMANDIRIAN BELAJAR - Ma'rup (Almeera Education, 2023)
Mathematics is one of the basic sciences that is very important to be taught to students. Mathematics subjects need to be given to all students starting from the elementary school level to equip students with the ability to think logically, analytically, systematically, critically, and creatively, as well as the ability to work together. The purpose of this study was to analyze the effect of the interaction of the Group Investigation (GI) learning method and independent learning on mathematics learning outcomes. This research was conducted at SMPN 17 Makassar. The affordable population in this study were class VII students of SMPN 17 Makassar. While the research sample was randomly selected from two classes from all class VII SMPN 17 Makassar assuming all classes were homogeneous. The research method used was quasi-experimental with the research hypothesis testing technique used was a two-way ANOVA with a 2 x 2 factorial. The data analysis requirements test used was the normality test and homogeneity test. The test results show that all data groups are normally distributed and homogeneous. The results of hypothesis testing showed that there was no interaction effect of the Group Investigation (GI) learning method and independent learning on mathematics learning outcomes. Based on the results of this study, efforts were made for teachers in learning mathematics to apply the Group Investigation (GI) learning method and seek to increase student learning independence.